X-ray fluorescence characterization of some medicinal plants traditionally used as aphrodisiac in the treatment of male sterility in Kenge City, Democratic Republic of the Congo - Mulwele, Frederick Ndombe; Ngbolua, Koto-Te-Nyiwa; Masens, B Yang Da Musa; Mbemba, Théophile Fundu; Mpiana, Pius Tshimankinda (Orapuh Journal, 2024)
Introduction Male infertility refers to the inability of a man to impregnate a woman. It is a public health issue among men of reproductive age. Certain minerals, such as zinc, selenium, iron, and magnesium, are essential to produce healthy sperm and for maintaining male reproductive function. Medicinal plants containing these minerals can improve sperm quality and increase the chances of conception in men suffering from infertility. Purpose The aim of this research was to analyze the elemental composition of four medicinal plants traditionally used for their aphrodisiac properties, with a particular emphasis on their application in the treatment of male sterility. Methods The mineral content of selected plants was assessed by X-ray fluorescence using Energy Dispersive XRF Spectrometer (EDXRF). Results The findings reveal significant concentrations of various minerals in the studied medicinal plants, providing crucial information about their elemental composition. Thirty mineral elements were identified, including six macro elements (Na, Mg, P, S, K, Ca), 15 micro elements (Al, Si, Mn, Ni, Cu, Mo, Pb, Ti, V, Cr, Hg, Br, Rb, Sr, and Cd), three important elements in the diet of spermatozoa (Fe, Zn, Mg), and seven non-relevant elements. These results can have direct implications for the medicinal properties of the plants, especially in the context of treating male sterility. Conclusions Among the selected medicinal plants, Mondia whitei is rich in minerals as evidenced by principal component analysis (PCA) and could potentially contribute to improving overall health and indirectly promoting male fertility. the